Synthesis New Polymeric Composite Materials Derivatives from thiosemicarbazide - Maha T. Sultan (Journal of Global Pharma Technology, 2020)
In this work tow monomers were prepared by using Thiosemicarbazide free-radical polymerization was used to polymerize monomers one with itself to produce tow polymers (P1, P2) and the second with Nano silica grafted meth acrylic acid to produce tow Nano composite (C1,C2) All the prepared compounds were characterized by FT-IR Spectroscopy. The structures of standard Nano silica and Nano composite were studied by Atomic Forces Microscopy (AFM).The X-ray diffraction offer information on molecular structure configuration of the Nano composite after modification which showed different in intensity between Nano silica and their Nano composite.Keywords: Triazole polymer, Nano composite, Modification.